Pores Functionalized Mesoporous Silica: An Original Approach for Hybrid Catalytic Materials - Mehdi, Ahmad (Current Organic Chemistry, 2014)
In the framework of developing new sustainable energy sources, the straining efforts of investing in the fabrication of novel chemicals and materials are governed by the escalating environmental constrains. Principally, catalysis domain has a major responsibility to cater to such constrains since it is capable of conducting reactions heightened by higher rates and higher selectivity towards the desired products. For instance, the development of new strategies for recycling catalysts that supersede complications and cost concerns can result in considerable economic and ecological benefits. The immobilization of catalytic functionality into inorganic matrices is of great interest in organic synthesis and green chemistry; not only for their higher selectivity and yields, but also for their advantageous heterogeneity, sustainability and positive environmental impact. In this context, this brief review provides a concise overview of functionalized mesoporous silica materials synthesized by assisted self-assembly process “soft way”, which consists of the hydrolysis and polycondensation reactions of silylated molecular precursors in the presence of surfactant that plays the role of structure-directing agent. Furthermore, the accessibly and the distribution of the organic moieties in the pores surface will be demonstrated through specific chemical modifications. Ultimately, several types of pores functionalized materials that act as organocatalysts will be described as well as their catalytic activities in metathesis, aldolisation and epoxydation.
Keywords: Functionalized pores